Media in Armed Conflicts: Is It Still a Good Idea? - Alshdaifat, Shadi; Hayajneh, Ahmad (Law, State and Telecommunications Review, 2021)
[Purpose] Many recent conflicts in different places in the world are considered as a perfect illustration of the growing risks faced by media working in conflict zones. It is therefore important to call renewed attention to the fact that direct harms against the media and its role are illegal based on the principles of international humanitarian law, which is the law that regulates the conduct of war (jus in bello) and protects civilian persons and objects, as long as they are not making an effective contribution to military action. The role of media and its great value cannot be considered a legitimate target in conflicts. Respectively, the media also benefit from all measures that must be taken by the conflicting parties measures –not confined to them alone– such as the principle of proportionality and the obligation to give a warning. As of late, many books and articles have been addressing the media in the time of conflicts. They all appear to discuss it either from one perspective, or consider its role concerning one single issue, but not daring to dive too deeply into specific related issues to the media in a time of conflicts. The purpose of this paper is to present evidence on how media plays a role in armed conflicts so that can help to prevent insecurity and violent conflict, and contribute to peace and justice. It aims to help recognize the importance of media and its positive and negative potential about conflicts. [Methodology] The paper will examine the available literature on this subject specifically focusing on the challenges faced by media and underlining the knowledge gaps around media in armed conflicts. [Findings] We have directed ourselves to approach the topic from a different perspective. We hope to accomplish it, in part, by introducing the role of media in armed conflicts and whether it is still a good idea.